Entrepreneurship skills in the curriculum of a selected vocational college in Selangor - et. al., Norlidah Alias, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Entrepreneurship is important in generating economic growth and social capital. Although entrepreneurship programs have been conducted in educational institutions, there seems to be uncertainty on components of entrepreneurship required in the curriculum. In addition, there has been very few successful entrepreneurs from these programmes. Further, there has been few studies onentrepreneurship in Malaysian Vocational Colleges and hence the implementation of programmes related to teaching entrepreneurship needs to be investigated to determine the skills required for entrepreneurship.A survey among 71 students and teachers at a premier vocational college to investigate current practices and EE components required was administered using a questionnaire and analysed using percentages and cross-tabulation while the open-ended responses were analysed according to emerging themes. The findings indicate that although EE was implemented in all colleges, the stakeholders required autonomy to design the curriculum according to the needs of the local community. Lack of resources and teacher preparedness were the main challenges in implementing EE. Marketing skills were required in most of the courses related to technology (Industrial Machinery Technology, Construction Technology and Computer and Networking System) whilesales management was important for Computer and Networking System, and Accountancy courses. Innovation was important for Electronic Technology. Further, some suggestions for the improvement of the vocational and technical courses in relation to entrepreneurship skills, were made.